Monitoring Home Sales Data with Optimization of Information Systems - Rahayu, Sri; Nurhaeni, Tuti; Pangestu, Panji Bangun (APTISI Transactions on Management (ATM), 2017)
PT. Sinar Property Group is a company that deals in home sales. Marketing Division of the company is the most dominating division in home sales data processing and it is very needed. Consumers data who buy a home become the basic reference in monitoring, it is also used for monitoring consumer payment transaction status and payment transaction archiving. The research is using SWOT as its method that used for knowing strength of the company, weakness, opportunity, and its threat. The results of the analysis show the company needs a system that capable to monitoring centered home sales data which functionally, marketing manager knows the total of consumer and total of sold home using a system which can be accessed in realtime using web-based system, so it will be easier in making decision. Keywords​: Sales, Monitoring, Sales Report, Website.